2007
DOI: 10.1002/smj.576
|View full text |Cite
|
Sign up to set email alerts
|

Strategic schemas, strategic flexibility, and firm performance: the moderating role of industry clockspeed

Abstract: We examine the moderating effect of industry clockspeed on the relationship between strategic schemas, strategic flexibility and firm performance. We employ two key properties of strategic schemas: complexity and focus. Using a sample of 225 firms from 14 industries, we show that the pattern of relationships among the theoretical constructs is different in fast-and slow-clockspeed industries. The results suggest that complexity of strategic schemas promotes strategic flexibility and success in fast clockspeed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
534
0
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 609 publications
(570 citation statements)
references
References 111 publications
12
534
0
3
Order By: Relevance
“…There have been studies investigating the manufacturing capability-performance link and the role of external characteristics of the environment such as the rate of innovation in industries (e.g., Nadkarni and Narayanan, 2007), environmental dynamism (e.g., Terjesen et al, 2011) and technological turbulence (e.g., Chavez et al, 2015a). It has been argued that organizations respond directly to external environments, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…There have been studies investigating the manufacturing capability-performance link and the role of external characteristics of the environment such as the rate of innovation in industries (e.g., Nadkarni and Narayanan, 2007), environmental dynamism (e.g., Terjesen et al, 2011) and technological turbulence (e.g., Chavez et al, 2015a). It has been argued that organizations respond directly to external environments, e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have shown that such focused attention can trigger strategic persistence and improved performance when industries are changing at a slow pace (Nadkarni and Narayanan 2007). For example, consistent with these top-down explanations, Polaroid's failure to profit from the commitment it made early to digital imaging technology stems from its top managers' inability to utilize the most appropriate structure of knowledge for changes that had occurred in the organizational environment.…”
Section: Transient Attention and Opportunity Identificationmentioning
confidence: 99%
“…Individuals learn core concepts from their prior experiences, which then become part of their knowledge structures (Nadkarni and Narayanan 2007;Walsh 1995). Core concepts generate particular environmental expectations that then guide how managers allocate attention in a topdown manner.…”
Section: High Levels Of Top-down Attention Allocation and Recognizingmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies flip the causal arrows examining how the external environment moulds strategic schema and behaviour. For example, Nadkarni and Narayanan (2007) highlight how the clock-speed of different industries shapes the complexity and focus of strategic schemas. Nadkarni and Barr (2008) examine how industry velocity shapes the structure of cognitive representations and the speed of strategic action.…”
Section: Cognition and Middle Managers' Strategy Knowledgementioning
confidence: 99%